Building an evidence base for adult safeguarding?: problems with the reliability and validity of adult safeguarding databases - Fyson, Rachel (Oxford University Press, 2015)
This article considers current adult safeguarding policy guidelines for England, which require local authorities to collect adult safeguarding data for the purposes of research and service development. It then moves on to report some of the findings from an evaluation of adult safeguarding in one English local authority, focussing on how the adult safeguarding database was populated from case records and how the resultant data was utilised. It found that, although the annual number of adult safeguarding alerts more than tripled between 2002 and 2008, this clear evidence of an increase in workload had not resulted in increased resource allocation. The evaluation further noted that only half of the designated ‘adult safeguarding managers’ who were interviewed were able to correctly define the meanings of the recommended terms under which adult safeguarding outcomes are recorded, i.e. ‘substantiated’, ‘not substantiated’ and ‘not determined’. Changes to the terminology used to record the outcomes of safeguarding investigations are proposed as one of a number of measures to enable the creation of valid and reliable information upon which to base future practice developments, including allocation of resources. Key